Assemblage, recruitment and ecology of fish larvae in Matang mangrove estuary and adjacent waters, Peninsular Malaysia / Ooi Ai Lin - Ooi, Ai Lin (2012)
Spatio-temporal distribution of larval fish in the Matang mangrove estuaries and adjacent coastal waters was examined from monthly surface horizontal tows from May 2002 to October 2003 at seven stations located 10.6 km upstream to 16 km offshore. A total of 92,934 fish larvae, representing 19 families were identified. A further 3 families were recorded in the mangrove waters during diel studies but not found during monthly samplings. Larval fish community using mangrove estuaries and nearshore waters mainly consists of a few key families of residents (e.g. Gobiidae) and euryhaline fishes (e.g. Engraulidae), whereas the wider diversity of other fish families in the estuary that were not collected as larvae suggest that they must have entered the estuary as juveniles. Larval fish assemblages were dominated by Gobiidae (50.1%) and Engraulidae, mainly Stolephorus baganensis and Thryssa kammalensis (38.4%). Larval fish abundance including their ontogenetic stages differed spatially and temporally. Three peaks of total larval fish were observed; March 2003 (992  986 N.100m-3), October 2003 (980 ± 1,440 N.100m-3) and August 2002 (656 ± 457 N.100m-3). These peaks coincided with the intermonsoon periods of variable winds and high rainfall, except the August peak when wind forcing was high. Two peaks of recruitment time were identified for Gobiidae in March and October. Spawning and resulting preflexion larvae of Engraulidae occurred between June to December in offshore waters, followed by the higher abundance of postflexion larvae between October-January in mangrove estuaries. Estuarine preflexion gobiid larvae were ubiquitous in the mangrove estuaries and coastal waters. Larval stages of euryhaline species such as Engraulidae and Clupeidae that spawned in offshore waters were largely advected into mangrove estuaries at the postflexion stage. Larvae of other euryhaline fishes (e.g. Sciaenidae, Blenniidae and Ambassidae) that likely spawned inside the estuary were, however, exported to offshore waters. Higher larval abundance was recorded during the wet period with twelve families identified for each period in the eight 24- hour samplings of surface and bottom layers in the lower estuary in July 2003 (dry period) and November 2003 (wet period). The yolk-sac stage of Gobiidae was more abundant at night during new moon when tidal inundation was highest. High numbers of preflexion gobiids were particularly observed at the end of ebb or flood tide (slack water), a strategy adopted for feeding during reduced water movement so as to maintain their position and retention within the estuary. Total Engraulidae larvae were more abundant at neap tide and younger preflexion larvae tended to aggregate in surface water during flood tide and day time. Postflexion larvae remained at the bottom of the estuary during ebb tide. The engraulid larvae appear to adopt a strategy for upstream penetration using the selective tidal transport during flood tide. Larval fish advection into or away from the estuary is by tidal currents but the final result of advection appears to be modulated by salinity and turbidity gradients, larval food availability, as well as larval stage and possibly larval behavior.